Mengontrol Kebebasan Perilaku Menggunakan Teknologi Digital dengan Digital Detox - Astrid Rahardaya (LPPM Stikosa - AWS, 2022)
The times have led to the emergence of various kinds of digital technologies that can be accessed easily. The emergence of various kinds of digital technology is an important necessity for many people. The uses of digital technology cannot be separated from everyday life. The uncontrolled frequency of using digital technology results in various kinds of bad impacts on humans, one of which is that it can lead to digital addiction. Although in essence humans are free creatures and have freedom of behavior in their daily lives, if this freedom is not controlled properly, it will harm many parties. To overcome this issue, Digital detox is needed so that humans can control their freedom in the use of digital technology.